EFIKASI DUA JENIS EKSTRAK TUMBUHAN DAN KOMBONASI KEDUANYATERHADAP MORTALITAS HAMA ULAT BAWANG MERAH (Spodoptera exigua Hubn) (LEPIDOPTERA: NOCTUIDAE) - Rifai, Muh.; Hasriyanty, Hasriyanty; Nasir, Burhanuddin (AGROTEKBIS, 2016)
The aims of this experiment were to obtain the effective and efficient concentrations of two kinds of plant extracts applied in single or in combination on the mortality of Spodoptera exiqua larva and to determine the LC50 value. This experiment used completely randomized design (CRD) with 5 treatments, namely A (K1 = 0.25%), B (K2 = 0.50%), C (K3 = 0.75%), D (K4 = 1.00%) and E (K5 = 1.25%) and each treatment was replicated 3 times. Larva used was instar 3. Results of this experiment showed that in a single test of Sidondo plant (Vitex negundo L.) extract, the concentration of 1% was effective with the LC50 value at 0.10% and mortality reached 83.33%; and Patah Tulang (Euphorbia tirucalli) extract, the concentration of 1% was also effective with the LC50 value at 0.08% and mortality was upto 83.33%. Combination of Sidondo and Patah Tulang plant extracts with 0.50% each was an effective concentration with LC50 value at 0.09% and mortality of Spodoptera exigua larvae at 48 hours after application reached 83.33%.Key Words: Euphorbia tirucalli, Land, Spodoptera exigua, Viteks negundo.